Biomass energy storage and geological safeguards in underground coal mine spaces - Qiang SUN; Chao GU; Jishi GENG; Yun WU; Yuliang ZHANG; Zhenlong GE; Zhen HUANG; Jianjun HU (Meitan kexue jishu)
Coal remains China’s primary energy source, with post-mining underground spaces offering both resource utilization opportunities and environmental risks. Efficient and sustainable development of these residual spaces is crucial for the coal industry’s future. This study systematically examines the utilization characteristics of underground coal mine spaces and the requirements for organic waste resource management. A comprehensive biomass energy storage framework based on the principles of Reduce, Reuse, Recycle, Renew, Restore, and Recover (6R) is introduced. This framework transforms abandoned underground areas into viable energy storage media, thereby facilitating the resource recovery of organic waste and elucidating the scientific attributes and implications of biomass energy storage coupled with geological safeguards. Three implementation pathways are proposed: aerobic utilization, anaerobic utilization, and pyrolysis-based utilization, each leveraging the inherent advantages of underground environments such as stability, constant temperature, and large capacity. Additionally, key scientific and technological challenges are identified, including environmental suitability assessment, spatial planning and optimization, geological property evolution monitoring, precise resource product utilization, and the cyclic regeneration of storage spaces. This research introduces innovative strategies for the efficient exploitation of underground coal mine spaces and the environmentally friendly treatment of organic waste. It facilitates the coal industry’s achievement of both capacity optimization and enhanced ecological performance.